Keterampilan Kerja dan Kompensasi Terhadap Kinerja Karyawan PT. Tunas Prima Sejahtera Kutai Kartanegara - Alya Syarah; Irsan Tricahyadinata; Abdul Rauf Alwi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study is motivated by the importance of employee performance in supporting organizational success, particularly in the plantation sector which requires high productivity and work effectiveness. Factors such as gender, work skills, and compensation are assumed to influence employee performance; however, previous studies have shown inconsistent results. Therefore, this study aims to examine the effect of gender, work skills, and compensation on employee performance at PT. Tunas Prima Sejahtera. This research employed a quantitative approach with a sample of 73 respondents determined using a non-probability sampling technique with a saturated sampling approach. Data were collected through questionnaires distributed to employees. The data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS software. The results show that gender does not have a significant effect on employee performance (p-value > 0.05), work skills have a positive and significant effect on employee performance (p-value < 0.05), and compensation has a positive but not significant effect on employee performance (p-value > 0.05). In conclusion, at PT. Tunas Prima Sejahtera, work skills are the most dominant factor in improving employee performance, while gender and compensation do not show a significant effect on employee performance.